2013
DOI: 10.1177/107327481302000204
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Human Epidermal Growth Factor Receptor 2 in Esophageal Cancer

Abstract: The importance of human epidermal growth factor-2 (HER2) in terms of prognosis and aggressiveness of growth has long been known in breast cancer, and interruption of its growth cascade by agents such as trastuzumab and lapatinib has markedly improved outcomes for these patients with HER2 overexpression. HER2 overexpression also occurs in many other tumor types, including esophageal cancer. In this disease, a different scoring system for determining overexpression is used. Limited data exist concerning the biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…In this era of molecular oncology, it is disconcerting that such a small proportion of patients received targeted therapy which has been associated with improved outcomes in a myriad of solid tumor indications. HER2 is overexpressed in 20–33% of EAC tumors, and EGFR is overexpressed in 25–30% of gastroesophageal tumors—demonstrating missed opportunities to potentially improve outcomes utilizing targeted therapies in our cohort (48, 49). Eight clinical trials testing EGFR targeted therapy with tyrosine kinase inhibitors (TKIs) vs chemotherapy in first-line non-small cell lung carcinoma demonstrated significant improvements in response rates and OS for every cohort treated with targeted therapy (50).…”
Section: Discussionmentioning
confidence: 96%
“…In this era of molecular oncology, it is disconcerting that such a small proportion of patients received targeted therapy which has been associated with improved outcomes in a myriad of solid tumor indications. HER2 is overexpressed in 20–33% of EAC tumors, and EGFR is overexpressed in 25–30% of gastroesophageal tumors—demonstrating missed opportunities to potentially improve outcomes utilizing targeted therapies in our cohort (48, 49). Eight clinical trials testing EGFR targeted therapy with tyrosine kinase inhibitors (TKIs) vs chemotherapy in first-line non-small cell lung carcinoma demonstrated significant improvements in response rates and OS for every cohort treated with targeted therapy (50).…”
Section: Discussionmentioning
confidence: 96%
“…Expression of HER2 is highly correlated with the prognosis of esophageal adenocarcinom [6], while the prognostic role in ESCC has hardly been investigated. We found that about 20 % of our patients were positive for HER2.…”
Section: Discussionmentioning
confidence: 99%
“…It is an important drug target for cancers, including breast cancer and gastroesophageal (GE) junction adenocarcinoma [67]. HER2 inhibition in combination with cisplatin-based chemotherapy has been demonstrated to significantly improve response rate and overall or progression-free survival in patients with adenocarcinoma of the gastro-esophageal junction or the stomach who over-express HER2 [7].…”
Section: Introductionmentioning
confidence: 99%
“…every 2 weeks. It is important to clarify that the use of trastuzumab as maintenance single agent beyond disease progression in the adjuvant or perioperative setting is not advised at this point outside of a clinical trial, and extrapolating data from the breast cancer literature and applying the same concepts in treating gastric and GEJ cancers is not recommended [86].…”
Section: Trastuzumabmentioning
confidence: 98%